186k views
5 votes
Help please need answer asap

Help please need answer asap-example-1
User Meriadec
by
4.9k points

2 Answers

0 votes

Answer:

f(x) = x - 3

Explanation:

y = mx + b

first let's find b, the y-intercept

based on the graph, the y-intercept is (0,-3), so b = -3

immediately, we can eliminate f(x) = 3 - x and f(x) = -3x

comment any questions pls

User Karl Stephen
by
4.5k points
2 votes

Answer:

f(x) = x -3

Explanation:

The y intercept is where it crosses the y axis. That value is -3

The slope is change in y over change in x

We start at the y intercept and go up +3 and to the right +3 to get to the next point.

The difference is +3/+3 = 1

The slope is 1

Putting this in slope intercept form

y = mx+b where m is the slope and b is the y intercept

y = 1x-3

or in function form

f(x) = x -3

User Bostrot
by
4.9k points